The Production Conditions of Biodegradable Film Containing Pomelo Peel Extract for Staphylococcus aureus Inhibition - Aichayawanich, Sawanit (วารสารสมาคมวิศวกรรมเกษตรแห่งประเทศไทย, 2016)
This research aimed at studying the production conditions of biodegradable film containing pomelo peel extract for Staphylococcus aureus inhibition. The effects of extracting solvents (95% ethanol, dichloromethane, hexane, and ethyl acetate) on yield and Staphylococcus aureus inhibiting activity of the pomelo peel extract were evaluated. Then, the influences of film process conditions; including drying temperatures (40, 45, 50, 55, and 60oC) and concentrations of pomelo peel extract (0.050, 0.075, 0.100, 0.125, and 0.150% w/w) on properties of the film were studied. The results showed that pomelo peel extract exhibited Staphylococcus aureus inhibition. Yield and Staphylococcus aureus inhibiting activity of the extract extracting by dichloromethane were the highest. The concentrations of the extract and drying temperatures had significant effect on the film properties. The highest tensile strength, percent elongation at break, and Staphylococcus aureus inhibiting activity were obtained from 0.150% (w/w) pomelo peel extract film that was dried at high temperature (60oC).